I am having some trouble understanding how to plug terms into the following sequence. I was given the following,

$$a_1=1, a_{n+1}=\frac{a_n}{\sqrt{n}}$$ for all n greater or equal to 1.

Plugging in terms we get the following,

$$a_1=1$$ $$a_2=a_1=1$$ $$a_3=\frac{a_2}{\sqrt{2}}=\frac{1}{\sqrt{2}}$$ $$a_4=\frac{a_3}{\sqrt{3}}=\frac{1}{\sqrt{6}}$$

How are they getting these terms $a_2,a_3,a_4$?


Notice that




Try to prove by induction that

$$a_{n+1}=\frac1{\sqrt{1\cdot2\cdot3\cdots n}}=\frac1{\sqrt{n!}}$$

  • $\begingroup$ why are the $a_1,a_2,a_3$ terms disappearing in the numerator? $\endgroup$ – jh123 Feb 14 '17 at 15:32
  • $\begingroup$ @jh123 Let's start with $a_2$. Do you understand that $a_2=\frac{a_1}{\sqrt1}$? From there, what is $a_1$? (check definition?) $\endgroup$ – Simply Beautiful Art Feb 14 '17 at 15:33
  • $\begingroup$ why would $a_2$ be equal to that? I thought $a_2=a_1+a_2$? $\endgroup$ – jh123 Feb 14 '17 at 15:34
  • $\begingroup$ Because $a_2$ was defined to be equal to that. Plug $n=1$ into the definition of the sequence. Why would $a_2=a_1+a_2$, which would require $a_1=0$? $\endgroup$ – Ross Millikan Feb 14 '17 at 15:37
  • 1
    $\begingroup$ @jh123 But don't forget to take a peak at the second part of my answer:$$a_{n+1}=\frac1{\sqrt{n!}}$$ $\endgroup$ – Simply Beautiful Art Feb 14 '17 at 15:55

They are using the definition. If you plug in $n=1$ you get $a_2=\frac {a_1}{\sqrt 1}=\frac 11=1.$ Then plug in $n=2$ to get $a_3=\frac {a_2}{\sqrt 2}=\frac 1{\sqrt 2}$ and so on.

  • $\begingroup$ why are the $a_1,a_2,a_3$ terms disappearing in the numerator? $\endgroup$ – jh123 Feb 14 '17 at 15:33
  • $\begingroup$ Because we plug in the value we know for them based on the earlier calculation. $\endgroup$ – Ross Millikan Feb 14 '17 at 15:36
  • $\begingroup$ so if $a_1=1$ then shouldn't $a_2 = \frac{a_1}{\sqrt{2}}= \frac{1}{\sqrt{2}}$ $\endgroup$ – jh123 Feb 14 '17 at 15:38
  • $\begingroup$ No, because we were taking $n=1$ and the denominator is $\sqrt n$, not $\sqrt {n+1}$ $\endgroup$ – Ross Millikan Feb 14 '17 at 15:56

We have that for $n \in \mathbb Z^+$, $$a_{n+1} = \frac {a _n}{\sqrt {n}} \tag {1}$$

Thus, using the relation $(1)$ successively, we get, $$a_2 = a_{1+1} = \frac {a_1}{\sqrt {1}} = \frac {1}{1} =1 $$ $$a_3 = a_{2+1} = \frac {a_2}{\sqrt {2}} = \frac {1}{\sqrt {2}} $$ $$a_4 = a_{3+1 } = \frac {a_3}{\sqrt {3}} = \frac {1}{\sqrt {2}\times \sqrt {3}} = \frac {1}{\sqrt {6}} $$

Hope it helps.

  • $\begingroup$ why is the $a_1$. $a_2$ $a_3$ terms disappearing in the numerator? $\endgroup$ – jh123 Feb 14 '17 at 15:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.